MULTIPARADIGMA DALAM ETIKA DAN AKHLAK KEPERILAKUAN DIBIDANG ILMU AKUNTANSI - Harfiahani Indah Rakhma Ningtyas (Institut Teknologi dan Bisnis Yadika, 2021)
Accounting is a system that produces financial information that is used by its users for making a decision. The purpose of the information is to provide guidance in choosing the best course of action in allocating scarce resources in economic business activities. Thus, accounting cannot be separated from human behavior that requires information. To carry out daily activities or the surrounding environment. So that accounting is not something passive, but accounting will always evolve throughout its era. In this study will discuss about a debate between academics and practitioners